Investigating Effective Factors in Maxillary Sinus Membrane Rupture and Its Treatment Methods: A Review - Nima Dehghani; Mohadeseh Azarsina; Xaniar Mahmoudi; Rahil Barani; Sahar Hassantash; Neshatafarin Manouchehri (Journal of Craniomaxillofacial Research)
Introduction: Maxillary sinus floor augmentation (MSFA) surgery is a reliable treatment for patients with atrophic posterior maxilla, which can be performed concurrently with or after implant installation. This study aimed to estimate the rate of sinus membrane perforation (SMP) during MSFA surgeries and examine various risk factors associated with SMP. The efficacy of perforation treatments was also evaluated. Materials and Methods: A systematic search of Scopus, PubMed, and Web of Science databases was conducted using the search terms: Implant AND Sinus AND Membrane AND Risk factor. Statistical analyses and graph creation were performed using Comprehensive Meta-Analysis (CMA) version 3. A total of 635 publications were screened, and 11 studies met the inclusion criteria, involving 1362 patients who underwent 1603 MSFA surgeries through the lateral window technique (LWT). Results: The prevalence of maxillary sinus membrane perforation among patients who had implants placed was 40.8% (Event: 0.331, 95% CI: 0.26-0.4). Implants placed near repaired perforated membranes demonstrated an average survival rate of 97.68%, whereas implants placed on intact sinus membranes had an average survival rate of 98.88%. Infection was identified as the primary complication associated with the repair of perforated sinus membranes. Conclusion: Despite the high incidence of sinus membrane perforation during MSFA surgeries, the survival rates of implants near repaired membranes are comparable to those placed on intact membranes. Appropriate antibiotic prescriptions can prevent infections, contributing to favorable surgical outcomes. Keywords: Maxillary sinus; Membrane rupture; Antibiotics; Survival rate.